Management of Auditory Hallucinations through Distraction Technique Training at Prof. Dr. Soerojo Psychiatric Hospital, Magelang - Sekar, Putri; Ainin Dita Prabaswala, Nyipta; Aliffiya Salsabilla, Nathasya; Khalimatus Sa’diyah, Afida; Mustain, Mukhamad (Proceedings of Conference on Health Universitas Ngudi Waluyo, 2026)
Schizophrenia is frequently accompanied by auditory hallucinations, which are often exacerbated by medication non-adherence and maladaptive coping mechanisms. This study aims to describe the management of sensory perception disturbance (auditory hallucinations) through structured hallucination management training, specifically utilizing distraction techniques, at RSJ Prof. Dr. Soerojo Magelang. This research employed a descriptive method with a case study approach, involving a 38-year-old female patient diagnosed with Paranoid Schizophrenia during the period of February 9–13, 2026. Data were collected via interviews, observation, and medical record documentation. Nursing interventions were implemented through four stages of Strategy Implementation (SP): assertive verbal command techniques (menghardik), medication adherence education (based on the "5 Rights" principle), social interaction techniques, and scheduled daily activities. The results demonstrate that these interventions were effective in reducing the frequency of hallucinations. The patient exhibited significant improvement in symptom recognition, the independent application of distraction techniques, and a reduction in social withdrawal behaviors. In conclusion, hallucination management utilizing distraction techniques, combined with medication adherence education, proved effective in enhancing patient independence. However, given the high history of relapse, successful long-term recovery necessitates a holistic approach, including the integration of family support and the continuity of post-discharge community mental health services to effectively prevent future relapse.